Does the Application of Platelet-Rich Fibrin in Anterior Cruciate Ligament Reconstruction Enhance Graft Healing and Maturation? A Comparative MRI Study of 44 Cases. Issue 2 (19th February 2020) - Beyzadeoglu, Tahsin; Pehlivanoglu, Tuna; Yildirim, Kerem; Buldu, Halil; Tandogan, Reha; Tuzun, Umit
Background: Anterior cruciate ligament (ACL) reconstruction performed with growth factors and activated platelets has been suggested to accelerate tendon ligamentization, leading to earlier return to daily activities and sports. Hypotheses: Platelet-rich fibrin (PRF) will result in improved graft maturation and healing as evaluated by magnetic resonance imaging (MRI) in patients undergoing hamstring ACL reconstruction. Hemostatic and analgesic properties of PRF will lead to less postoperative blood loss and pain. Study Design: Cohort study; Level of evidence, 3. Methods: A total of 44 patients with isolated ACL injuries who underwent arthroscopic all-inside anatomic single-bundle ACL reconstruction with semitendinosus tendon graft were enrolled. Group 1 included 23 patients who had PRF sprayed to the surface of the graft; group 2 included 21 patients for whom no PRF was used. Patients were discharged after 24 hours and examined for hemarthrosis that needed to be aspirated. MRI was performed at the fifth postoperative month. A blinded radiologist evaluated graft maturation according to its signal intensity and the presence of synovial fluid at the tunnel-graft interface. Results: PRF-treated grafts demonstrated lower MRI signal intensity and less fluid in the graft-tunnel interface as compared with controls for the entire length of the graft. The mean full-length MRI signal intensities were 9.19 versus 16.59 ( P = .047) for groups 1 and 2, respectively. Subgroup analysis of the semitendinosus grafts demonstrated a signal intensity of 11.57 versus 23.98 ( P = .044) for the proximal third, 9.53 versus 13.83 ( P = .237) for the midbody, and 6.48 versus 11.98 ( P = .087) for the distal third. Synovial fluid at the graft-tunnel interface was detected in 1 patient in group 1 (4.3%) and 3 patients in group 2 (14.3%; P < .001). Patients in group 1 had significantly less hemarthrosis that needed to be aspirated ( P = .003), while postoperative analgesia requirements were similar in both groups ( P = .08). No clinical benefit of PRF could be demonstrated in clinical outcomes. Conclusion: Application of PRF led to superior graft integration and maturation in the proximal third of the ACL graft. There was no significant difference in MRI signal intensity in the midbody or distal tibial graft. Application of PRF also resulted in significantly lower rates of postoperative hemarthrosis that needed to be aspirated.